Dual representations of the rural in Brazilian cinematography: implications for education - José Leite dos Santos Neto; Afrânio Mendes Catani (Universidade Federal do Norte do Tocantins, 2021)
There is a strong cinematographic representation that establishes rural and urban in a dichotomous relationship that commonly sustains the speech of rural articulated to social issues and inequality and naturalizes this representation. In order to subsidise the pedagogical practice of teachers on the critical stance of the rural and the urban, this paper aims to question how the representations of the rural have been approached by the audio-visual language. The analysis has a qualitative approach and combines methodological procedures of documentary, historiographic and film analysis. Therefore, it is approached in a historical perspective the dual discourse that represents the peasant; in the sequence it is discussed the correct conceptions of territorial delimitation, and finally, presented, in a sample of films, the synthesis of representations that follows the same line of systematic and progressive arguments of representation of the rural and the urban. The research points to the conclusion regarding the importance of school, to subsidise critical reading about the representations covered in films, which overcomes the dichotomous view that naturalizes social problems as particular to the rural.